Ultrasmall inorganic nanoparticles repair damaged meningeal lymphatic vessels to boost Parkinson’s disease therapy - Mengxiao Han; Yaobao Han; Zhilin Jiang; Yifan Gao; Guozhi Cao; Hao Zhang; Tingting Wang; Zhen Li (Proceedings of the National Academy of Sciences, 2025)
Meningeal lymphatic vessels (MLVs) have been identified to associate with various neurological diseases, such as traumatic brain injury (TBI), Alzheimer’s disease (AD), Parkinson’s disease, multiple sclerosis, and brain tumors. Damage to MLVs can exacerbate the pathological progression of these diseases and significantly impede therapeutic efficacy. Therefore, targeted repair of the damaged MLVs has emerged as an innovative strategy for treating these central nervous system (CNS) diseases. In this study, we find that inorganic Cu 2− x Se nanoparticles, rather than conventional endogenous vascular endothelial growth factor-C (VEGF-C), can repair the damaged MLVs to restore their structure and functions. These nanoparticles not only promote the growth and development of lymphatic vessels but also enhance the drainage capacity of impaired MLVs, thereby facilitating the transport of immune cells and macromolecules through these vessels. Unlike the conventional repair of damaged MLVs, this is an instance where inorganic nanoparticles have been explored to stimulate the expression of VEGF-C and its receptor VEGFR3, thereby promoting the structural and functional recovery of these vessels. The enhanced drainage function of MLVs mediated by Cu 2− x Se nanoparticles significantly alleviates the symptoms of pre-formed fibrils (PFFs)-induced Parkinson’s disease in mice. Collectively, our findings demonstrate that inorganic nanoparticles can promote the growth and development of meningeal lymphatics like VEGF-C, providing a cost-effective and innovative strategy for repairing damaged MLVs to boost the therapeutic efficacy of CNS diseases.